Deformation of the Macumber Formation, Antigonish Basin, Nova Scotia: implications for the Ainslie Detachment - Thomas, D.; Nance, R.; Murphy, J. (Atlantic Geology, 2003)
ABSTRACT The Antigonish Basin is one of several Carboniferous structural basins in northeastern Nova Scotia, the evolution of which have been cited as evidence for major detachment faulting within the Vis. Windsor Group of Maritime Canada. Evidence of extension in the Antigonish Basin takes the form of a major subhorizontal structure that closely follows the basin margins and has been interpreted as part of the regional Ainslie Detachment. Placed at the top of the basal Macumber Formation and reportedly characterized by several metres of calc-mylonite, the detachment is considered to have accommodated 10—25 km of westward transport of the evaporitic Windsor and overlying Mabou groups during the late Namurian-early Westphalian. However, deformation within the Macumber Formation limestone immediately beneath the detachment surface suggests local extension of Vis. age. Recumbent intraformational folds are overlain by depositional breccias that contain previously folded fragments and are themselves recumbently folded. These relationships suggest repeated movement that began soon after limestone deposition. Furthermore, fold asymmetry and the orientation of calcite veins and small-scale normal faults suggest variable directions of extension that converge on the centre of the basin located in St. Georges Bay. While these data do not preclude the existence of the Ainslie Detachment, they suggest that the Macumber Formation in the Antigonish Basin records an earlier episode of deformation that occurred in response to local gravity sliding rather than to movement on a regional detachment surface.